2006
DOI: 10.1007/s11010-006-9212-9
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin must be acetylated in order to form a complex with membrane Na+,K+-ATPase and to inhibit its enzyme activity

Abstract: In cells of neural and non-neural origin, tubulin forms a complex with plasma membrane Na(+),K(+)-ATPase, resulting in inhibition of the enzyme activity. When cells are treated with 1 mM L-glutamate, the complex is dissociated and enzyme activity is restored. Now, we found that in CAD cells, ATPase is not activated by L-glutamate and tubulin/ATPase complex is not present in membranes. By investigating the causes for this characteristic, we found that tubulin must be acetylated in order to associate with ATPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 30 publications
6
49
0
Order By: Relevance
“…and K ? -ATPase activity [165][166][167][168][169]. Expression of an acetylation-resistant a-tubulin mutant significantly inhibits adipogenesis [170], suggesting that adipocyte differentiation is dependent on tubulin acetylation.…”
Section: Tubulin Acetylation In Stress and Other Signaling Pathwaysmentioning
confidence: 99%
“…and K ? -ATPase activity [165][166][167][168][169]. Expression of an acetylation-resistant a-tubulin mutant significantly inhibits adipogenesis [170], suggesting that adipocyte differentiation is dependent on tubulin acetylation.…”
Section: Tubulin Acetylation In Stress and Other Signaling Pathwaysmentioning
confidence: 99%
“…In addition to mitochondrial membranes, tubulin has been shown to interact with proteins associated with other membranes (14,15). Tubulin is a heterodimer, composed of similar 50-kDa globular ␣ and ␤ subunits.…”
mentioning
confidence: 99%
“…In an interesting model, Jackson [101] discussed the possible role of N-terminal acetylation of GTPases, and subsequent association of this enzyme with membrane, a process that further influences membrane trafficking and organelle structure in eukaryotic cells. Cytoskeletal proteins such as cytokeratins [102], tubulin [103][104][105] and myosin [99,106] can also be acetylated, and this PTM can influence their association with the plasma membrane. Casale et al [103] and Santander et al [104] have shown that the brain plasma membrane Na 1 , K 1 -ATP-ase is inhibited by acetylated tubulin.…”
Section: Acetylationmentioning
confidence: 99%
“…Cytoskeletal proteins such as cytokeratins [102], tubulin [103][104][105] and myosin [99,106] can also be acetylated, and this PTM can influence their association with the plasma membrane. Casale et al [103] and Santander et al [104] have shown that the brain plasma membrane Na 1 , K 1 -ATP-ase is inhibited by acetylated tubulin. Moreover, tubulin must be acetylated in order to form a complex with this enzyme [105].…”
Section: Acetylationmentioning
confidence: 99%